The Legal Conundrum of Electoral Dispute Settlement Regarding the Candidacy Threshold - Fathurokhman, Ferry; Rayhan, Ahmad; Karsa, Pipih Ludia; Gunawan, Muhammad Safaat (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2025)
This study addresses the persistent challenges in Indonesian electoral dispute resolution and candidacy threshold regulations, a recurring issue in both general and regional elections, notably in 2024. The urgency lies in the need for robust legal frameworks to ensure fair and democratic processes. Employing a normative juridical method with legal, historical, comparative, and conceptual approaches, this research offers novel insights into optimizing dispute settlement mechanisms. It proposes empowering Bawaslu, KPU, and DKPP for proactive and reactive oversight, alongside advocating for candidacy threshold adjustments aligned with prevailing laws and Constitutional Court rulings on presidential thresholds. This research contributes by offering concrete policy recommendations for a more stable and just electoral system.